An exploratory QUALquan comparison of patient‐centeredness priorities in outpatient Care for Patients and Pharmacists. Issue 6 (3rd April 2022) - Olson, Anthony W.; Isetts, Brian J.; Stratton, Timothy P.; Vaidyanathan, Rajiv; Hillman, Lisa A.; Schommer, Jon C.
Abstract: Introduction: Evidence‐based practice is necessary for improving chronic disease prevention, reduction, and management while simultaneously lowering care costs. Patient‐centeredness encompasses one of three essential and overlapping components of evidence‐based practice, the others being clinical expertise and scientific/research evidence. While patient‐centered care was placed at the center of the Joint Commission of Pharmacy Practitioners Pharmacists' Patient Care Process (PPCP), few studies investigate the concept's meaning in outpatient pharmacist care. Objectives: This study explores the meaning of patient‐centeredness from the perspectives of patients and their pharmacists participating in outpatient care consistent with the PPCP, and compares the elements that matter most between these two groups. Methods: Data for this exploratory QUALquan mixed methods study were collected via in‐depth interviews designed to elicit perceptions of what matters to patients in pharmacist care from a purposive sample of adult patients with multiple chronic conditions and their outpatient pharmacists in the United States. Data were assessed using directed content analysis informed by 40 seminal patient‐centeredness concepts from the health professional literatures of medicine, nursing, and health policy. Results: Data analysis produced 13 distinct superordinate concepts representing the meaning of patient‐centeredness in the context of the PPCP. The perceived importance of the patient‐centeredness superordinate concepts was generally consistent between patients and pharmacist groups except for "Therapeutic Alliance, " "Care Coordination and Integration, " and "Care Experience." Conclusion: This study's superordinate concepts of patient‐centeredness adds clarity for what matters to patients in pharmacist care encounters, key elements for organizing team‐based systems to meet the unique needs of each patient, and upstream factors that can facilitate or prevent patient‐centered care. Future research should assess the reproducibility of the findings, explore reasons behind patient‐pharmacist priority differences, and evaluate the resulting impact.